2004
DOI: 10.1097/00005721-200401000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Common Menstrual Disorders in Adolescence: Nursing Interventions

Abstract: Menstrual disorders such as amenorrhea, excessive uterine bleeding, dysmenorrhea, and premenstrual syndrome are common reasons for visits to healthcare providers by adolescent girls. Although menstrual irregularity can be normal during the first few years after menarche, other menstrual signs and symptoms may indicate a pathological condition that requires prompt attention and referral. This article discusses four common menstrual disorders seen in adolescent girls and focuses on specific nursing interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 12 publications
2
24
0
1
Order By: Relevance
“…Nursing efforts toward empowering the adolescent to assume responsibility for her body are likely to be more effective than efforts aimed at compliance (McEvoy et al, 2004). Partially consistent with some earlier reports in the West (Banikarim et al, 2000;Helms, 1987;Hewison & Akker, 1996;Klein & Litt, 1981), it appears that Taiwanese adolescents may not always use medications effectively and would benefit from additional information on period pain management.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Nursing efforts toward empowering the adolescent to assume responsibility for her body are likely to be more effective than efforts aimed at compliance (McEvoy et al, 2004). Partially consistent with some earlier reports in the West (Banikarim et al, 2000;Helms, 1987;Hewison & Akker, 1996;Klein & Litt, 1981), it appears that Taiwanese adolescents may not always use medications effectively and would benefit from additional information on period pain management.…”
Section: Discussionsupporting
confidence: 53%
“…Within the Chinese paradigm, liver-qi stagnation causes women's blood to stagnate in the uterus, leading to periods of pain (Maciocia & Kaptchuk, 1998). Primary dysmenorrhea is the leading cause of recurrent short-term school absenteeism among American (Klein & Litt, 1981;McEvoy, Chang, & Coupey, 2004) and Taiwanese (Chen, 1982) adolescent girls. Jarrett, Heitkemper, and Shaver (1995) found that the most commonly reported strategy for cramping pain was the use of medication among American women with dysmenorrhea between 21 and 44 years of age.…”
mentioning
confidence: 99%
“…Menstrual disorders form the commonest gynecological complaint (45-58%) among adolescents, yet are often overlooked [1,2] Though the onset of menstruation is part of the normal maturation process, variability in menstrual cycle characteristics and menstrual disorders are common. The common menstrual disorders reported in adolescents are amenorrhea, abnormal/excessive uterine bleeding, dysmenorrhea and premenstrual syndrome which can be effectively diagnosed and treated in the adolescent population [3].…”
Section: Introductionmentioning
confidence: 99%
“…3,6e8 Pre-menstrual syndrome (PMS) refers to symptoms such as acne, fatigue, bloating, anger, and moodiness. 9 PMS affects between 14% and 89% of adolescents. 10,11 Scott et al reported that twice as many AfricanAmerican adolescents felt unprepared and did not receive information about menarche when compared with Caucasian teens.…”
Section: Introductionmentioning
confidence: 99%